The monopole problem in holographic cosmology - Nastase, Horatiu [UNESP]; Portugal, Ulisses M. [UNESP] (Elsevier, 2021)
In this letter we clarify that the monopole problem can always be solved in bosonic holographic cosmology, by the analogue of “dilution” in inflation, which is the fact that the electric current is an irrelevant operator in the dual field theory. We show that not only specific toy models solve the problem, but any purely bosonic member of the phenomenological class, of super-renormalizable, generalized conformal symmetric models.